Edukacja młodzieży z perspektywy idei CSR - Wolska, Grażyna (Humaniora. Czasopismo Internetowe, 2024)
Progress in all areas of socio-economic activity depends on the level of education. In contemporary literature, “education” is interpreted in various ways. Many theories, concepts and education systems are proposed. Issues related to education and its key role in promoting the idea of corporate social responsibility are also discussed. The aim of the study is to prove that the currently adopted education system requires modernization towards a dialogic method of teaching applied ethics and CSR.